Lifestyle INtervention for Diabetes prevention After pregnancy (LINDA-Brasil): study protocol for a multicenter randomized controlled trial. Issue 1 (December 2016) - Schmidt, Maria; Duncan, Bruce; Castilhos, Cristina; Wendland, Eliana; Hallal, Pedro; Schaan, Beatriz; Drehmer, Michele; Costa e Forti, Adriana; Façanha, Cristina; Nunes, Maria
Abstract Background Gestational diabetes mellitus (GDM), a hyperglycemic state detected during pregnancy, is an established risk factor for diabetes. However, treatment during pregnancy in and of itself is not able to eliminate this risk, and a considerable fraction of women with GDM will develop frank diabetes in the decade following pregnancy. Our aim is to conduct a multicenter randomized controlled trial to investigate the effectiveness of a lifestyle intervention program implemented after a pregnancy complicated by GDM in delaying or preventing the development of type 2 diabetes. Methods Women aged 18 or older identified as having recent GDM are recruited and followed by telephone to assess eligibility for the trial. To be eligible, women must have used insulin during pregnancy or present intermediate hyperglycemia postpartum. Women are encouraged to enter the trial as early as 10 weeks, and are permitted to do so up to 2 years after a pregnancy with GDM. An estimated 740 women will be randomized to either conventional care or to coach-based interventions focused on breastfeeding, weight loss, healthy eating, and increased physical activity, and predominantly delivered by telephone. Women are followed annually to detect new onset diabetes, the primary outcome, and additional secondary outcomes which include reversion to normoglycemia, weight loss, physical activity and fitness, and insulin resistance. Discussion Though previous studies have demonstrated that type 2 diabetes can be delayed or prevented, no study has yet demonstrated the feasibility and effectiveness of similar interventions implemented in the postpartum period for women with recent GDM. If shown to be successful, this approach could become an important means of preventing diabetes in primary care settings. Trial registration ClinicalTrials.gov Identifier:NCT02327286 ; Registered 23 December 2014.